Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Budaya Disiplin Siswa di MAS Patra Mandiri Plaju Palembang - Surya, Sandy; Zainuri, Ahmad; Habiburrahman, Sayid (Prodi PAI STAI Sumatera Medan, 2020)
Discipline culture is a reflection of the quality of educational institutions. The low level of discipline is the main problem of every educational institution. The role of leadership is very much needed in overcoming this problem. This paper aims to describe the leadership role of madrasah principals in improving the disciplinary culture of students at MAS Patra Mandiri Plaju Palembang. This research uses a qualitative approach with a descriptive analytic study method. Data were collected using interview techniques, observation and documentation study. The results of this study indicate that the headmaster of MAS Patra Mandiri Plaju Palembang has played its role and function in improving the disciplinary culture of students in a fairly good category. This is supported by 2 factors, namely (1) the role models of madrasah principals in complying with school regulations; and (2) socialization of school discipline rules and sanctions for violations. The obstacles faced by madrasah principals are (1) there are still some teachers who do not exemplify student attitudes; and (2) there are still students who are not